PECULIARITIES OF PHYSICAL AND MENTAL DEVELOPMENT OF PRESCHOOL CHILDREN (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The main task of physical education of preschool children is to direct them to early education and to ensure their desire for physical activity.